Comparative Reading of Motherhood Identities in East African and Indonesian Literature - Stanley Elias (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
The study comparatively examines the representation of motherhood identities and the trauma of being childless to women in African and Indonesian literary texts namely Ngugi wa Thiong’o’s Secret Lives and other Stories, Elieshi Lema’s Parched Earth, Ratih Kumala’s Genesis and Iwan Setyawan’s Ibuk. Central to the analysis of this study is the argument that the existing cultural and religious discourses significantly contribute to the ways motherhood identities are construed in the society. Of a particular note, motherhood is argued to be a desired position that every woman wants most and is ready to sacrifice for it. Importantly, marriage, religious orientations and orders of the patriarchy certify motherhood and its related identities in the society. On the other hand, childlessness or failure to bear a male child circumscribe women in reduced forms of their identities and so subjects them to psychological and physical trauma and of course a social stigma.